"Misturar tudo": a autoria na escrita de Helder Macedo - Pires, Nayara Meneguetti (2022)
The novels written by Helder Macedo, despite being very different from each other, are known for what they have in common: the crossing of borders, both with regard to the limits between real and fictional, as well as the borders between literary and discourse genres. To that, joins the presence of characters who have the author's own name and characteristics, as well as the metafictional commentary and the affiliation to a certain literary tradition, the same about which his essays are a reference. In this way, one work ends up pointing to another, as well as directing to his poems and essays, which address the same themes. This characteristic has already led his critical fortune to affirm the possibility of looking at his work as a self-referential set, however, it is still necessary to think about this constant pointing outwards and the insistent presence of the author in the narrative - through the selection of intertextualities, as well as through characters or metafictional comments - are configured as an erasure of the notion of autonomy of the work of art and the death of the author. In this sense, it is worth thinking about how the figure of this author is constructed and what place he claims for himself within the literary space when he criticizes modern rationality, which is the purpose of this thesis.